Influence of experimental parameters on iron oxide nanoparticle properties synthesized by thermal decomposition: size and nuclear magnetic resonance studies. (27th February 2018) - Belaïd, Sarah; Stanicki, Dimitri; Vander Elst, Luce; Muller, Robert N; Laurent, Sophie
Abstract: A study of the experimental conditions to synthesize monodisperse iron oxide nanocrystals prepared from the thermal decomposition of iron(III) acetylacetonate was carried out in the presence of surfactants and a reducing agent. The influence of temperature, synthesis time and surfactant amounts on nanoparticle properties is reported. This investigation combines relaxometric characterization and size properties. The relaxometric behavior of the nanomaterials depends on the selected experimental parameters. The synthesis of iron oxide nanoparticles with a high relaxivity and a high saturation magnetization can be obtained with a short reaction time at high temperature. Moreover, the influence of surfactant concentrations determines the optimal value in order to produce iron oxide nanoparticles with a narrow size distribution. The optimized synthesis is rapid, robust and reproductive, and produces nearly monodisperse magnetic nanocrystals.